Demandas e competências nas práticas docentes no curso de administração de empresas: bacharelado - Conti, Sérgio L (2010)
Considering the importance of training teachers of undergraduate courses in Business Administration and, taking into account the increase in the number of places offered for the course for the last three decades, this paper seeks to show "whether” and “how "teachers of a particular University Center has been preparing themsilves to meet the requeriments to role this function. Given what has been stated the study aims to understand the processes of construction practices of professors of business administration and reveal the criteria by which them plan and execute their pedagogical actions. In a context in which training for teaching in higher education is grounded in research and considering the what is requered According to CNE No. 4 of 2005 which established the National Curriculum Guidelines for the Management course, this study has the chance to verify “whether” and "as" Institutions of Higher Education and their teachers have been sought to comply suit demand and on the other hand, taking as background the demands and responsabilities of international economic scenarios, as well as the challenges arise for teachers on this metter, requiring mobilization for the development of teaching strategies for effective action in the contemporary context. The study involved thirty professors of Administration - Bachelor Degral from an institution of higher learning in São Paulo, whose’s names will be kept confidential, and the work is called ALFA University Center and was held in 2010. In the rescarch, it was concluded that teachers have difficulties in organizing their educational material, since half of them are unaware of the principal documents of the course, which is the Education Programme of the Course and Institutional Development Plan. Besides, it was found that there is little criteria in the conduct, on the actions of teachers and the planning, and implementation of pedagogical actions. A positive aspect was that two thirds of teachers said they participate in training courses for teachers. In the context of international financial crisis, only a third of teachers said their stance in the classroom was affected and half of the teachers pointed out that had not changed their lesson strategies. The research showed also that the initiative before the crisis to the discussions about the phenomenon was the teacher. Setting up the problem, is presented in this work, the methodological choice is conducting a qualitative research, and interviews were conducted with teachers of the University Center for ALFA which hypotheses could be proven or not